The effectiveness of occupational health policies in promoting HIV/AIDS management within organisations - Skeepers, Natalie Carol (Stellenbosch : University of Stellenbosch, 2011)
Thesis (MPhil (Industrial Psychology. Africa Centre for HIV/AIDS Management))--University of Stellenbosch, 2011.